Nematophilic bacteria associated with entomopathogenic nematodes and drug development of their biomolecules - Awori, Ryan Musumba (Frontiers in Microbiology, 2022)
The importance of Xenorhabdus and Photorhabdus symbionts to their respective Steinernema, and Heterorhabditis nematode hosts is that they not only contribute to their entomopathogenicity but also to their fecundity through the production of small molecules. Thus, this mini-review gives a brief introductory overview of these nematophilic bacteria. Specifically, their type species, nematode hosts, and geographic region of isolations are tabulated. The use of nucleotide sequence-based techniques for their species delineation and how pangenomes can improve this is highlighted. Using the Steinernema-Xenorhabdus association as an example, the bacterium-nematode lifecycle is visualised with an emphasis on the role of bacterial biomolecules. Those currently in drug development are discussed and two potential antimalarial lead compounds are highlighted. Thus, this mini-review tabulates forty-eight significant nematophilic bacteria and visualises the ecological importance of their biomolecules. It further discusses three of these biomolecules that are currently in drug development. Through it, one is introduced to Xenorhabdus and Photorhabdus bacteria, their natural production of biomolecules in the nematode-bacterium lifecycle, and how these molecules are useful in developing novel therapies.